(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Elevated serum ammonia levels are associated with hepatic encephalopathy(HE). This study was designed to evaluate the correlation between ammonia levels and grades of HE. This study was conducted in Shalamar teaching hospital Lahore. 50 patients suffering from liver cirrhosis and presenting with altered sensorium were recruited in the study. Their serum ammonia levels, Child Pugh score, and grades of hepatic encephalopathy were determined, and correlated. Serum ammonia was normal in 18(36%) and it was high in 32(64%) patients. 15(30%) patients had grade I, 16(32%) patients had grade II, 12(24%) patients had grade III and 7(14%) patients had grade IV of hepatic encephalopathy. Conclusion: There is positive weak correlation between ammonia levels and grades of hepatic encephalopathy. Ammonia is etiologically linked but it is not solely responsible for the increasing severity, of hepatic encephalopathy.